Methodological Recommendations for Adopting the Structurationist Perspective on Organizational Studies - Rossoni, Luciano; Filho, Edson Ronaldo Guarido; Coraiola, Diego Maganhoto (Organizações & Sociedade, 2013)
This paper discusses the use of Giddens' structuration theory in the field of organizationstudies. Under this approach, we discuss some methodological implicationsthat can improve coherence to the research based on the premises and hypothesisof structuration theory in the field. Four assumptions were initially treated: socialreality as an intersubjective product, the principle of duality of structure, the doublehermeneutic in social research and the structural positioning as a relevant issue forresearching agency. Moreover, methodological recommendations were presented bearing on three fundamental aspects: the definition of level of analysis, the choiceof the temporal range and the design of methodological procedures, considering twointerdependent levels of the research process. The first level considers the hermeneuticelucidation of meanings and forms of practical consciousness, while the second dealswith the constraints of agency and the temporal-spatial context. Taken together, weconclude in favor of long-term research projects, when based on Giddens' structurationtheory.